2019
DOI: 10.23958/ijirms/vol04-i02/584
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infant Mortality in Samdrup Jongkhar District, Bhutan

Abstract: Samdrup Jongkhar district has reported an increasing trend in infant mortality rates over the recent years. This study aimed to identify its determinants. A population based case-control study was conducted in May 2018. Case group comprised of 79 infants who died between 1st January 2015-30th April 2018 while 158 living children born during the same period and residing closest to the home where infant mortality occurred were recruited as controls. Premature new-borns and those with low birth weight were 5.9 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…A case-control study found that children who were born premature and had low birth weight had higher odds of dying. In contrast, children of mothers who attended antenatal and postnatal care were less likely to die before reaching their first birthday (Pokhrel et al, 2019). More than 50% of the deaths were found to occur at home.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A case-control study found that children who were born premature and had low birth weight had higher odds of dying. In contrast, children of mothers who attended antenatal and postnatal care were less likely to die before reaching their first birthday (Pokhrel et al, 2019). More than 50% of the deaths were found to occur at home.…”
Section: Introductionmentioning
confidence: 84%
“…More than 50% of the deaths were found to occur at home. This study by Pokhrel et al (2019) was conducted in one district that prohibits generalizability and did not examine the influence of some important factors such as solid fuel use, water and sanitation, education of husband and household head, domestic violence, and rural residence. Another study showed that the mother's age, parity, region of residence, household size, and access to electricity and sanitation were factors predicting under-five-year-old mortality in Bhutan (Dendup et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over half (56%) of these under-five deaths are neonatal death as reported by the National Health Survey of Bhutan 2012 8 . Similarly, a study conducted to identify the determinants of infant mortality in Samdrup Jongkhar District of Bhutan reported that around one-third of the infant deaths were contributed by neonatal deaths 9 .…”
Section: Introductionmentioning
confidence: 99%